THE IMPACT OF COMPENSATION AND WORK ENVIRONMENT TOWARD EMPLOYEE PERFORMANCE AT PT. JAGAAMAN SARANA - Putri, Najwa Nurmaliza; Sary, Fetty Poerwita (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This study aims to The years from 2020 to 2023 in Indonesia were marked by economic turmoil, impacting sectors like mining due to a combination of external and domestic factors. This research, centered on PT. Jagaaman Sarana in the mining industry, delves into the relationship between compensation, work environment, and employee performance, aiming to provide insights into how these factors influence employee performance during challenging economic times. This study examines compensation disparities and the effects of work environment on employee performance at PT. Jagaaman Sarana, a significant player in Indonesia's mining sector. The findings offer valuable insights for enhancing employee well-being and optimizing performance within the mining industry. The method that is used in this research is quantitative approach with purpose of descriptive research, the data werre collected through many sources and proceeeded by statistical program in Smart PLS. Object in this research is PT. Jagaaman Sarana, the independent variabel in this research is Compensation and Work Environment where the dependent variabel is employee performance. The study at PT. Jagaaman Sarana underscores a crucial nexus between compensation, work environment, and employee performance in the demanding mining industry. Rigorous tests, including robust validity and reliability assessments, affirm a substantial positive correlation. Compensation and an improved work environment collectively contribute significantly, explaining a noteworthy 67% of the variance in enhanced employee performance. These findings highlight the strategic imperative of optimizing compensation structures and cultivating positive work environments, as they play a dominant role in driving a remarkable three-quarters of the observed performance improvements. This chapter's insights provide a compelling blueprint for organizations aiming to meticulously refine their human resource management strategies, offering a potent formula for achieving not just satisfactory but superior employee performance in the dynamic landscape of the mining sector